Manfaat Pendidikan Islam - Radiansyah Radiansyah; Anjas Baik Putra; Nur Azizah; Siti Khalijah Simanjuntak (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The benefits of Islamic Education are for the future, that is, it can increase or expand our knowledge of Allah and His creation, in religious science or general science can also strengthen and increase the faith of students in instilling islamic teachings and can directly, the benefits of Islamic education in the effectiveness of the Qur'an are interpreted in Surah al-Taubah verse 122 and al-Mujadalah verse 11 these verses are found in it about the benefits of Education then interpreted and was unfaithfully munasabahkan by well-known mufassir. So that these verses can be used as a reference basis in conveying and explaining the importance of the benefits of Islamic education. Keywords: Islamic Education, Benefits of Qur'anic verses.